Model of School Preparedness Policy in Earthquake Disaster Mitigation and Volcanic Eruption at Senior High School in Bukittinggi - Fitria, Rini (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose of this research 1) to determine the model of school preparedness policy in the earthquake disaster, 2) to know the model of school preparedness policy in volcanic eruption problems. Type of research used quantitative and qualitative research (Mixed Method) that use in a research activity and supported by using SWOT analysis techniques and AHP (Analytical Hierarchy Process). The result of this research Model of school preparedness policy in earthquake disaster mitigation that is; (1) Strengthening governance, transparency, and accountability of earthquake disaster management, (2) Conducting training through extracurricular scouts at schools, (3) Preparing curriculum on disaster early. While the model of school preparedness policy in mitigating the catastrophic eruption of volcano namely; (1) to build social capital of disaster school responses for eruption of volcano eruption, (2) to relocate schools close to dangerous zone of volcanic eruption, (3) making design of psychology recovery program for school society in disaster of volcano eruption.